Representasi Perempuan dalam Game Simulasi Kencan Picka: 30 Days to Love 2 - Virginia Swastika; Abdul Firman Ashaf; Purwanto Putra (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
Women in games are often portrayed with negative narratives. They are often cast as objects of lust through their physical appearance, and are taken for granted. However, dating simulation games provide a different perspective on women. This research aims to unravel how women are represented in dating simulation games, specifically in the game 30 Days to Love 2 which carries the concept of dating reality show. To analyze the phenomenon, this research uses Roland Barthes semiotics which reveals meaning through denotation and connotation signs. The results show that women in dating simulation games have been viewed more positively. However, female attributes such as appearance are still attached to gender stereotypes that emphasize beauty standards.